Pengaruh Kinerja Baznas Terhadap Kesejahteraan Masyarakat di Indonesia Tahun 2001-2020 - Yeubun, Shimah Fauziah; Yuliana, Indah (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aims to examine the performance of the National Amil Zakat Agency (BAZNAS) which is an institution that manages zakat funds for the welfare of the people in Indonesia. Performance measurement by calculating the ratio of fiscal performance, public support, and efficiency of fundraising. In addition, people's welfare by looking at the Human Development Index (IPM). The research method used is descriptive quantitative with secondary data types, namely BAZNAS financial statements and HDI figures with an observation period from 2001 to 2020. The data analysis technique uses multiple linear regression with statistical evaluation tools 12. The results show that fiscal performance, public support, and efficiency fundraising do not partially affect the welfare of the people in Indonesia. Furthermore, the simultaneous test shows that the performance of BAZNAS which consists of fiscal performance, public support, and efficiency funding does not simultaneously affect the welfare of the people in Indonesia.